Analisa Manajemen Risiko Pada Travel Umroh Menggunakan Matriks Manajemen Risiko : Studi Kasus “Travel Umroh Rawda Cahya Multazam” Di Kota Bandung - Panji Setia Meijaya; Nayla Rubayyina Nugraha; Asep Rizal Asep Rizal; Muhammad Luthfi Mubarrok; Alfiana Alfiana (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze risk management at Umroh Travel Rawda Cahya Multazam, an umrah travel agency in Bandung, using a risk matrix approach. A descriptive qualitative method was applied through interviews to identify various risk categories, including market, financial, marketing, operational, human resources, and legal risks. Risk assessment was conducted using likelihood and impact criteria, resulting in the classification of risks into low, medium, and high levels. The findings reveal 22 identified risks, consisting of 8 high-level risks, 13 medium-level risks, and 1 low-level risk. The most critical risks include fluctuations in ticket and hotel prices, delayed customer payments, intense competition, currency exchange volatility, logistical issues, regulatory changes, and visa processing delays. Based on the evaluation, several mitigation strategies are recommended, such as long-term pricing contracts, strengthened standard operating procedures, digital marketing optimization, staff training, diversified package offerings, and establishing an emergency fund. The study concludes that systematic risk management enhances operational stability, increases customer trust, and strengthens the company’s competitiveness amid uncertainties in the umrah travel industry.